(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2022)
An online active torque pulsation reduction strategy for rotational systems with position-dependent loading torque (such as crankshaft-based loads) driven by grid-connected induction machines is proposed. The control strategy requires system speed and induction machine torque information. No stiff parameters are necessary for the closed-loop control strategy. The theoretical principle is simulated and experimentally validated.